Cardiorenal outcomes in eligible patients referred for bariatric surgery. Issue 12 (1st November 2021) - Dash, Satya; Everett, Karl; Jackson, Timothy; Okrainec, Allan; Urbach, David R.; Sockalingam, Sanjeev; Shah, Baiju R.; Farkouh, Michael E.
Abstract: Objective: Bariatric surgery is associated with reduced atherosclerotic cardiovascular disease (CVD) and heart failure hospitalization in people with type 2 diabetes (T2D) and those with prior CVD. Most patients undergoing bariatric surgery do not have T2D or CVD. Many otherwise eligible patients do not have surgery because of self‐exclusion. Clinical outcomes in these groups are less established. Methods: This study retrospectively assessed cardiorenal outcomes in 8, 568 patients after acceptance of referral for surgery. Results: A total of 63.8% patients did not undergo surgery. After multivariate adjustment for sex, age, BMI, income quintile, distance from hospital, hypertension, T2D, and CVD, hazard ratios (HR) for the primary (incident myocardial infarction, stroke, heart failure hospitalization, and death; HR = 0.52, 95% CI: 0.4‐0.66) and secondary CVD outcomes (primary outcomes and coronary/carotid revascularization; HR = 0.53, 95% CI: 0.42‐0.67) were lower in the surgery cohort. This reduction was seen in those with (primary: HR = 0.45, 95% CI: 0.32‐0.63, secondary: HR = 0.47, 95% CI: 0.34‐0.65) and without T2D (primary: HR = 0.61, 95% CI: 0.42‐0.88, secondary: HR = 0.53, 95% CI: 0.42‐0.67). Reduced kidney disease (HR = 0.46, 95% CI: 0.22‐0.92) but increased liver disease hospitalization (HR = 2.5, 95% CI: 1.45‐4.27) was observed with surgery. Conclusions: Non‐progression to surgery associates with increased CVD despite low baseline prevalence of CVD. The cardiorenal benefits of bariatric surgery warrant confirmation in a well‐powered randomized clinical trial.